Laboratory facilities for investigating lipid disorders in the United Kingdom: results of the British Hyperlipidaemia Association survey. Issue 2 (February 1992) - Laker, M F; Reckless, J P; Betteridge, D J; Durrington, P N; Miller, J P; Nicholls, D P; Shepherd, J; Thompson, G R
Abstract : AIMS: To determine the availability of facilities for the investigation of hyperlipidaemia in the United Kingdom. METHODS: A questionnaire was sent to all health districts in the United Kingdom. RESULTS: The response rate was 81%. All laboratories used enzymatic techniques to measure serum triglyceride and cholesterol concentrations, although there were differences in standardisation procedures. Reference ranges for serum lipids were quoted by 58% of laboratories while 50% quoted "desirable limits". Almost half specified that fasting blood samples were required. High density lipoprotein cholesterol concentrations were estimated by 75% and apolipoproteins AI and B by 14% of laboratories; there were differences in specimen type and considerable diversity in procedures used for measurement. CONCLUSIONS: Many laboratories were unaware of current recommendations for screening for hypercholesterolaemia in the community. The present survey indicated an urgent need for the introduction of better reference methods, standardisation, and quality assurance procedures before apolipoproteins become a routine part of coronary heart disease risk assessment.